2002
DOI: 10.1080/00420980220099087
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood Effects and Cultural Exclusion

Abstract: The idea of neighbourhood effects implies that the demographic context of poor neighbourhoods instills 'dysfunctional' norms, values and behaviours into youths, triggering a cycle of social pathology. It is argued that neighbourhood effects are part of a wider discourse of inner-city marginality that stereotypes inner-city neighbourhoods. Reflecting upon arguments made in the existing literature, the ideological underpinnings of the idea of neighbourhood effects are revealed. Essentialist conceptions of neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
12

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 49 publications
2
76
0
12
Order By: Relevance
“…Alternative, and widely discredited, arguments about the culture-of-poverty and the underclass (Bauder, 2002), as well as deficit models of parenting which are still in evidence in some areas of primary schooling (Primary Review, 2007), are also apparent. This is evident in the way headteachers discuss the perceived deficiencies of local cultures, for example as low-income communities are seen to be limited by low aspirations, and by a lack of cultural know how.…”
Section: Problematising Parental Aspirationsmentioning
confidence: 99%
“…Alternative, and widely discredited, arguments about the culture-of-poverty and the underclass (Bauder, 2002), as well as deficit models of parenting which are still in evidence in some areas of primary schooling (Primary Review, 2007), are also apparent. This is evident in the way headteachers discuss the perceived deficiencies of local cultures, for example as low-income communities are seen to be limited by low aspirations, and by a lack of cultural know how.…”
Section: Problematising Parental Aspirationsmentioning
confidence: 99%
“…Living in a stigmatized neighbourhood has been found to have a negative influence on the residents' job opportunities (Bauder, 2002;Wilson, 1996) and self-esteem (Taylor, 1998). It has also been suggested that neighbourhood reputations can have an effect on the behaviour of residents, who may adjust their social actions (within and outside their neighbourhood) in accordance with the area's ill repute among outsiders (see for example Galster and Killen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, these explanations seek to impose unfair blame on the disadvantaged themselves for economic and social problems rather than taking account of broader structural processes. Nonetheless, Bauder (2002) contends that in practice, the concept of 'community effects' is applied simplistically and uncritically leaving the way open for use as a political tool to blame communities for their own exclusion. Likewise, as Kintrea and Atkinson (1998) argue in the UK regeneration context, it is one thing to suggest as Wilson does that social networks are important; however, it is quite another to propose, as happens in regeneration, that government can rebuild more socially integrated, cohesive, inclusive and sustainable communities through introducing middle-income home owners into social housing estates.…”
Section: Introductionmentioning
confidence: 99%